Irrigation management of durum wheat in the Mitidja plain (Algeria): water balance models comparison and validation - Leulmi S.; Sellam F. (Drought management: scientific and technological innovations, 2008)
In Algeria cereal crops are confronted with adverse constraints which include the irregularity of rainfall and the variability of the climate. The water remains the main factor which explains the variations of crop yields because the drought can appear at any time during the cultural cycle. Within the framework of research projects conducted in the Department of Rural Engineering of the National Agronomic Institute, two models concerning the complement irrigation were tested on cereals over the Mitidja plain in the experimental station at the National Institute Agronomy (Algiers). The experimental station is located under a Mediterranean climate. The trials were realized with a durum wheat culture variety Vitron during three campaigns 1999/2000, 2000/2001 and 2001/2002 with devices including differentiated irrigation regimes. The main objective of these experiments was to validate two water budget simulation models, Bilhyna (INRA, Paris, France) and Pilote (CEMAGREF, Montpellier, France). The main difference of these two models is that Bilhyna includes the estimation of deep water fluxes by means of finite difference resolution of the Richard's equation while Pilote uses the principle of reservoirs limited by the maximum root depth.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)